The making of a mammalian peroxisome, version 2.0: mitochondria get into the mix - Schrader, Michael (Cell Death Differ, 2017)
A recent report from the Laboratory of Heidi McBride (McGill University) presents a role for mitochondria in the de novo biogenesis of peroxisomes in mammalian cells. Peroxisomes are essential organelles responsible for a wide variety of biochemical functions, from the generation of bile to plasmalogen synthesis, reduction of peroxides, and the oxidation of very-long-chain fatty acids. Like mitochondria, peroxisomes proliferate primarily through growth and division of pre-existing peroxisomes. However, unlike mitochondria, peroxisomes do not fuse; further, and perhaps most importantly, they can also be born de novo, a process thought to occur through the generation of pre-peroxisomal vesicles that originate from the endoplasmic reticulum. De novo peroxisome biogenesis has been extensively studied in yeast, with a major focus on the role of the ER in this process; however, in the mammalian system this field is much less explored. By exploiting patient cells lacking mature peroxisomes, the McBride laboratory now assigns a role to ER and mitochondria in de novo mammalian peroxisome biogenesis by showing that the formation of immature pre-peroxisomes occurs through the fusion of Pex3-/Pex14-containing mitochondria-derived vesicles with Pex16-containing ER-derived vesicles.